Pengaruh Trend Memes Marketing Core Tiktok @Idevicestore Terhadap Brand Awareness - Rana Ashilah Zahra; Gibbran Prathisara (Riviera Publishing, 2025)
This study aims to determine the extent of the influence of TikTok's memes marketing core trend by @iDeviceStore on Brand Awareness, focusing on its impact on user engagement, brand perception, and increased product visibility. The background of this research stems from the massive use of social media as a marketing platform, especially TikTok, which has become one of Indonesia's most popular social media, possessing great potential to enhance brand awareness through engaging and viral content. This research is an explanatory study with a quantitative approach. Data were analyzed using simple linear regression technique to measure the influence of the independent variable content marketing through memes marketing core trends on the dependent variable Brand Awareness. The results show that the use of memes marketing core trends on the @iDeviceStore TikTok account has a significant impact on increasing Brand Awareness. The contribution of this strategy to Brand Awareness reaches 70.1%, indicating that meme-based content is effective in shaping perception, strengthening brand recall, accelerating brand recognition, and influencing consumer purchase intention. In conclusion, memes marketing core is a relevant and adaptive content marketing strategy on TikTok for positively increasing brand awareness.